Similarity Detection in Android Screen: a comparative analysis using Information Retrieval, Embeddings and Vision Language Models - Souza, Daniel Augusto R. Lima de; Ramos, Fabio C.; Oliveira, Cainã S. de; Veras, Edluce L.; Lopes, Paulo Fabricio da F.; Santos, Barbara L.; Souza, Jose Diogo B. de; Oliveira, Adriano De O. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15052, 2025)
The growing mobile application development market brings an urgent need for tools capable of evaluating and comparing similarities between screens of different applications. This article proposes a comparative analysis of methods for similarity detection on Android screens, integrating Information Retrieval (IR), embedding models (BGE-M3, Snowflake-Arctic-Embed2, Nomic-Embed-Text) and Vision Language Models (VLM) such as qwen2.5vl:7b and gemma-3:27b. The study addresses challenges like design redundancies and UI test inconsistencies by using combined pipelines: IR, embeddings, and VLM for screen identification. The results demonstrate the strengths and limitations of each approach, providing insights into their applicability in mobile UI similarity detection.